Organic Anion Transporting Polypeptide Inhibition Dramatically Increases Plasma Exposure but not Pharmacodynamic Effect nor Inferred Hepatic Intracellular Exposure of Firsocostat. Issue 5 (25th November 2020) - Kirby, Brian J.; Lutz, Justin D.; Yue, Mun Sang; Garrison, Kimberly L.; Qin, Ann Ran‐Ran; Ampaw, Lorraine; Beysen, Carine; Myers, Robert P.; Kearney, Brian P.; Mathias, Anita
Abstract : Firsocostat (FIR: previously GS‐0976), a highly sensitive OATP substrate, reduces hepatic de novo lipogenesis (DNL) by inhibiting acetyl‐CoA carboxylases (ACC). Measuring the pharmacodynamic (PD) efficacy of FIR on DNL provides a unique opportunity to determine optimal dosing strategies for liver‐targeted OATP substrates in settings of altered OATP function. A randomized, four‐way crossover drug‐drug interaction study was conducted. Hepatic DNL, a marker for ACC activity, was measured in 28 healthy volunteers after reference, single dose FIR 10 mg, FIR 10 mg plus the OATP inhibitor rifampin (RIF) 300 mg i.v., or RIF 300 mg i.v. (control for DNL effect of RIF), each separated by a 7‐day washout. Samples were collected for pharmacokinetic (PK) and PD assessments through 24 hours after each treatment. Hepatic DNL and its inhibition by FIR were assessed. Twenty‐four subjects completed the study. All adverse events were mild. RIF alone increased hepatic DNL area under the effect curve from time of administration up to the time of the last quantifiable concentration (AUEClast ; 35.7%). Despite a 5.2‐fold increase in FIR plasma exposure (area under the concentration‐time curve from zero to infinity (AUCinf )) when administered with RIF, FIR alone, and FIR + RIF had the same hepatic PD effect, 37.1% and 34.9% reduction in DNL AUEClast, respectively, compared with their respective controls. These findings indicate that large decreases in OATP activity do not alter hepatic intracellular exposure (as inferred by no change in PD) for drugs that are primarily eliminated hepatically and permeability rate‐limited, such as FIR. These results support PK theory that has been difficult to test and provide practical guidance on administration of liver‐targeted drugs in settings of reduced OATP function.